Dominant-negative mutations in human IL6ST underlie hyper-IgE syndrome. - Béziat, Vivien; Tavernier, Simon J; Chen, Yin-Huai; Ma, Cindy S; Materna, Marie; Laurence, Arian; Staal, Jens; Aschenbrenner, Dominik; Roels, Lisa; Worley, Lisa; Claes, Kathleen; Gartner, Lisa; et al. (J Exp Med, 2020)
Autosomal dominant hyper-IgE syndrome (AD-HIES) is typically caused by dominant-negative (DN) STAT3 mutations. Patients suffer from cold staphylococcal lesions and mucocutaneous candidiasis, severe allergy, and skeletal abnormalities. We report 12 patients from 8 unrelated kindreds with AD-HIES due to DN IL6ST mutations. We identified seven different truncating mutations, one of which was recurrent. The mutant alleles encode GP130 receptors bearing the transmembrane domain but lacking both the recycling motif and all four STAT3-recruiting tyrosine residues. Upon overexpression, the mutant proteins accumulate at the cell surface and are loss of function and DN for cellular responses to IL-6, IL-11, LIF, and OSM. Moreover, the patients' heterozygous leukocytes and fibroblasts respond poorly to IL-6 and IL-11. Consistently, patients with STAT3 and IL6ST mutations display infectious and allergic manifestations of IL-6R deficiency, and some of the skeletal abnormalities of IL-11R deficiency. DN STAT3 and IL6ST mutations thus appear to underlie clinical phenocopies through impairment of the IL-6 and IL-11 response pathways.
Keywords: Adolescent; Alleles; C-Reactive Protein; Cell Membrane; Cells, Cultured; Child; Cytokine Receptor gp130; Cytokines; Female; Fibroblasts; Genes, Dominant; Genetics, Population; HEK293 Cells; Humans; Job Syndrome; Kinetics; Loss of Function Mutation; Male; Middle Aged; Models, Biological; Mutation; Pedigree; Phenotype; Th2 Cells; Up-Regulation; Young Adult

Multiplexed Functional Assessment of Genetic Variants in CARD11. - Meitlis, Iana; Allenspach, Eric J; Bauman, Bradly M; Phan, Isabelle Q; Dabbah, Gina; Schmitt, Erica G; Camp, Nathan D; Torgerson, Troy R; Nickerson, Deborah A; Bamshad, Michael J; Hagin, David; Luthers, Christopher R; et al. (Am J Hum Genet, 2020)
Genetic testing has increased the number of variants identified in disease genes, but the diagnostic utility is limited by lack of understanding variant function. CARD11 encodes an adaptor protein that expresses dominant-negative and gain-of-function variants associated with distinct immunodeficiencies. Here, we used a "cloning-free" saturation genome editing approach in a diploid cell line to simultaneously score 2,542 variants for decreased or increased function in the region of CARD11 associated with immunodeficiency. We also described an exon-skipping mechanism for CARD11 dominant-negative activity. The classification of reported clinical variants was sensitive (94.6%) and specific (88.9%), which rendered the data immediately useful for interpretation of seven coding and splicing variants implicated in immunodeficiency found in our clinic. This approach is generalizable for variant interpretation in many other clinically actionable genes, in any relevant cell type.
Keywords: Adenine; B-Cell CLL-Lymphoma 10 Protein; B-Lymphocytes; CARD Signaling Adaptor Proteins; Cell Line; Diploidy; Exons; Genes, Dominant; Genetic Variation; Guanylate Cyclase; Humans; Immunologic Deficiency Syndromes; Jurkat Cells; Lymphoma; NF-kappa B p50 Subunit; Piperidines; Polymorphism, Single Nucleotide; Primary Immunodeficiency Diseases; Sensitivity and Specificity